Design and development of a semi‐autonomous agricultural vineyard sprayer: Human–robot interaction aspects1. Issue 8 (29th May 2017) - Adamides, George; Katsanos, Christos; Constantinou, Ioannis; Christou, Georgios; Xenos, Michalis; Hadzilacos, Thanasis; Edan, Yael
Abstract: This article presents the design aspects and development processes to transform a general‐purpose mobile robotic platform into a semi‐autonomous agricultural robot sprayer focusing on user interfaces for teleoperation. The hardware and the software modules that must be installed onto the system are described, with particular emphasis on human–robot interaction. Details of the technology are given focusing on the user interface aspects. Two laboratory experiments and two studies in the field to evaluate the usability of the user interface provide evidence for the increased usability of a prototype robotic system. Specifically, the study aimed to empirically evaluate the type of target selection input device mouse and digital pen outperformed Wiimote in terms of usability. A field experiment evaluated the effect of three design factors: (a) type of screen output, (b) number of views, (c) type of robot control input device. Results showed that participants were significantly more effective but less efficient when they had multiple views, than when they had a single view. PC keyboard was also found to significantly outperform PS3 gamepad in terms of interaction efficiency and perceived usability. Heuristic evaluations of different user interfaces were also performed using research‐based HRI heuristics. Finally, a study on participants' overall user experience found that the system was evaluated positively on the User Experience Questionnaire scales.